The association between female sexual function and metabolic features of the polycystic ovary syndrome in Turkish women of reproductive age. - YOLDEMİR, AHMET TEVFİK (My University, 2024)
Objective: To investigate the association between female sexual function and metabolic features among women with polycystic ovary syndrome (PCOS) during reproductive age. Method: This was a cross-sectional study in which 288 women with PCOS and 180 women without PCOS between the ages of 20 and 40 years were evaluated. All women had serum total testosterone, androstenedione, DHEA-S, fasting glucose, total cholesterol, HDL-C, LDL-C, and triglyceride levels analyzed. The McCoy Female Sexual Questionnaire (MFSQ) was applied to all studied women. Exploratory factor analysis and reliability analysis were done after data collection. The factor loadings of MFSQ domains were compared between women with PCOS and controls. Results: Average factor loadings of the MFSQ sexuality domain and MFSQ sexual partner domain were significantly lower in the PCOS group when compared to controls. There was no correlation between the two sexual function domains of the MFSQ and the PCOS features either in the PCOS group or the controls. Conclusion: PCOS is a heterogeneous disease with different metabolic components, such as insulin resistance, obesity, and hyperandrogenism. Although sexual function among women with PCOS was lower than controls, no differences were found in metabolic features of the PCOS and non-PCOS groups with relation to sexual function determined by the MFSQ.
Keywords: Polycystic ovary syndrome; female sexual dysfunction; sexual satisfaction; sexuality; questionnaire; McCoy female sexual questionnaire